Studi Keanekaragaman Makrozoobentos Di Sungai Tanjung Pinggir Kecamatan Siantar Martoba Kota Pematang Siantar Provinsi Sumatera Utara - Elifal Tensadon Siagian; Ria Retno Dewi Sartika Manik; Mardame Pangihutan Sinaga (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
Tanjung Pinggir River is a river in the city of Pematang Siantar. In this river, there are various types of macrozoobenthos which are very influential for the ecosystem in the river. The aim is to determine the diversity of macrozoobenthos and the dominant macrozoobenthos type in the Tanjung Pinggir River, Pematang Siantar City. The types of macrozoobenthos found in the Tanjung Pinggir River were the Ampullaridae family of 47 individuals, the Cyrenidae family of 26 individuals, the Unionidae family of 29 individuals, the Thiaridae family of 36 individuals, the Lumbricidae family of 39 individuals, so that the total found was 168 individuals. The diversity value in the Tanjung Pinggir River is 1.59 in the moderate category. If per station then divided into 4 stations. At station I the diversity value was 1.54 with the moderate category, at station II the diversity value was 1,30 with the medium category, at station III the diversity value was 1.06 with the medium category and at station IV the diversity value was 0.50 with the low category. The highest dominance value is the Ampullaridae family with a value of 0.078 and the lowest is family Cyrenidae with a value of 0, 024.